An Investigation of the Mineral in Ductile and Brittle Cortical Mouse Bone. (16th April 2015) - Rodriguez‐Florez, Naiara; Garcia‐Tunon, Esther; Mukadam, Quresh; Saiz, Eduardo; Oldknow, Karla J; Farquharson, Colin; Millán, José Luis; Boyde, Alan; Shefelbine, Sandra J
ABSTRACT: Bone is a strong and tough material composed of apatite mineral, organic matter, and water. Changes in composition and organization of these building blocks affect bone's mechanical integrity. Skeletal disorders often affect bone's mineral phase, either by variations in the collagen or directly altering mineralization. The aim of the current study was to explore the differences in the mineral of brittle and ductile cortical bone at the mineral (nm) and tissue (µm) levels using two mouse phenotypes. Osteogenesis imperfecta model, oim ‐/‐, mice have a defect in the collagen, which leads to brittle bone; PHOSPHO1 mutants, Phospho1 ‐/‐, have ductile bone resulting from altered mineralization. Oim ‐/‐ and Phospho1 ‐/‐ were compared with their respective wild‐type controls. Femora were defatted and ground to powder to measure average mineral crystal size using X‐ray diffraction (XRD) and to monitor the bulk mineral to matrix ratio via thermogravimetric analysis (TGA). XRD scans were run after TGA for phase identification to assess the fractions of hydroxyapatite and β‐tricalcium phosphate. Tibiae were embedded to measure elastic properties with nanoindentation and the extent of mineralization with backscattered electron microscopy (BSE SEM). Results revealed that although both pathology models had extremely different whole‐bone mechanics, they both had smaller apatite crystals, lower bulk mineral to matrix ratio, and showed more thermal conversion to β‐tricalcium phosphate than their wild types, indicating deviations from stoichiometric hydroxyapatite in the original mineral. In contrast, the degree of mineralization of bone matrix was different for each strain: brittle oim ‐/‐ were hypermineralized, whereas ductile Phospho1 ‐/‐ were hypomineralized. Despite differences in the mineralization, nanoscale alterations in the mineral were associated with reduced tissue elastic moduli in both pathologies. Results indicated that alterations from normal crystal size, composition, and structure are correlated with reduced mechanical integrity of bone. © 2014 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals, Inc. on behalf of the American Society for Bone and Mineral Research.